2015
DOI: 10.1016/j.aidm.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Delayed healing of gastric ulcer is associated with downregulation of connexin 32 in the gastric mucosa

Abstract: Summary Background/Aims Most benign gastric ulcers are healed through suppression of gastric acid by a proton pump inhibitor (PPI). Despite prolonged use of a PPI, some gastric ulcers still do not heal. The primary goal of this study is to investigate the relationship between the expression of connexin 32 (Cx32), a major gap junction protein expressed in the gastric mucosa, and the healing response of gastric ulcers. Methods Patients with endoscopically verified gastric ulcer were treated with a standard dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The immunohistochemical results of the PCNA indicated proliferations occurring in the gastric tissue following Brexin application. This result agrees with Wang et al (2015). They demonstrated that Pantoprazole showed an increase in immunoreactivity to PCNA whether following prostaglandin application or at treatment with H2 receptor antagonist alone in the gastric tissue.…”
Section: Discussionsupporting
confidence: 89%
“…The immunohistochemical results of the PCNA indicated proliferations occurring in the gastric tissue following Brexin application. This result agrees with Wang et al (2015). They demonstrated that Pantoprazole showed an increase in immunoreactivity to PCNA whether following prostaglandin application or at treatment with H2 receptor antagonist alone in the gastric tissue.…”
Section: Discussionsupporting
confidence: 89%
“…Differences between this study and Okada et al's study regarding the proportions of patients with healed ulcers are therefore mainly due to differences in sample size and patients' age. Given the high efficacy of PPIs for the treatment of gastric ulcers 4 , it is more likely that differences in the proportions of ulcer healing between this study and literature data 5 are due to the fact this study was underpowered to detect the total healing effect of PPIs in this population.Nevertheless, low expression of connexin 32 on the gastric mucosa of patients included in this study is also a possible explanation to the much lower rate of ulcer healing observed, compared with literature data 5,15 .Systematic research of this marker on patients' gastric mucosa would have been helpful to verify this hypothesis. The fact that a delay of repeat endoscopy > 8 weeks was a predictor of non-healing of the ulcer in this study suggests that when patients came to do repeat endoscopy beyond the 8 th week, it was because they suspected nonhealing of the ulcer due to persistent or worsening symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…The C-terminal of claudin binds to the zonula occludens through their PDZ domains to seal the TJ (Nomme et al, 2015 ). Dysregulation of these proteins along with another gap junction protein CX32 expressed in gastric mucosa has been reported in delayed healing of gastric ulcer thus leading to gastritis or carcinoma (Wang et al, 2015 ). Activation or deactivation of these proteins under various stimuli is studied in this study.…”
Section: Methodsmentioning
confidence: 99%